Effects of a Community-Based Intervention on the Lifestyle and Health of People at Risk of Type 2 Diabetes in Benin - METONNOU, Ericie Hermeline; AZANDJEME, COLETTE SYLVIE; SOSSA, JÉRÔME CHARLES; Issiako, Bio Nigan; AGUEH, VICTOIRE DAMIENNE AGOSSI (My University, 2022)
Introduction: Worldwide, the prevalence of type 2 diabetes (T2D) is increasing at an epidemic rate. The objective of this study was to measure the effects on lifestyle intervention in subjects at risk of T2D in a West African country. Methods: This study involved Beninese adults at risk of T2D randomly selected from 2 groups of villages: control villages and villages exposed to nutrition education, cooking demonstrations and physical activity sessions. Anthropometric, clinical, and biological measurements were taken in both groups at the beginning and end of the intervention, which lasted 12 months. The paired sample t-test was used to assess the effect of the intervention on the lifestyle of people at risk of T2D. Results: After 12 months of exposure to nutrition education, cooking demonstrations and physical activity sessions in the intervention villages, the mean body mass index, waist circumference, body fat percentage, blood glucose, triglycerides, total cholesterol and amount of alcohol consumed per week had significantly decreased. Conversely, the mean intensity of physical activity and food consumption score had significantly increased. In the control group, 5.6% of the people at risk developed to diabetes. The relative risk was RR = 0.20 [0.14 - 0.56]. Conclusion: The intervention significantly improved metabolic indicators, intensity of leisure activity and dietary score. We suggest larger studies to better assess the effect of community-based interventions on the lifestyle and health of people at risk of T2D in Africa.
Keywords: Effects; Primary Prevention; People at Risk of Type 2 Diabetes; Benin